South Africa’s Land Ownership System as a Barrier to Social Transformation - Nancy Andrew (Revue Internationale des Études du Développement, 2020)
Racially based land ownership continues to create conflict, and like the capitalist system it anchors, has blocked meaningful social transformation since the end of formal apartheid. Failed land reform is partly a reflection of global processes increasingly shaping dynamics within South Africa and other countries, accelerating the concentration of land ownership and agriculture, with a sharp downward effect on the rural poor. Through the prism of the extensive displacement of farm labour families from white commercial farms, based on two periods of research since 1996, the article looks at the social relations of property and production, as well as the conflicts between owners and farm labour – labour tenants and farmworkers. They centre on farm owners’ strong opposition to tenure reform and land rights, illustrating not only the social impact but the barriers to change that these relations help to maintain.